2022
DOI: 10.1177/09567976221119391
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety Does Not Predict Exam Performance When Knowledge Is Controlled For: Strong Evidence Against the Interference Hypothesis of Test Anxiety

Abstract: Do test-anxious students perform worse in exam situations than their knowledge would otherwise allow? We analyzed data from 309 medical students who prepared for a high-stakes exam using a digital learning platform. Using log files from the learning platform, we assessed students’ level of knowledge throughout the exam-preparation phase and their average performance in mock exams that were completed shortly before the final exam. The results showed that test anxiety did not predict exam performance over and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…*This element was identified through Turkish participants' responses. (Theobald et al, 2022). Moreover, from the perspective of the emotional information processing model, students' recognition of knowledge deficits before and during evaluative events likely influences their appraisal of the learning event and subsequent affective response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*This element was identified through Turkish participants' responses. (Theobald et al, 2022). Moreover, from the perspective of the emotional information processing model, students' recognition of knowledge deficits before and during evaluative events likely influences their appraisal of the learning event and subsequent affective response.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the study skills deficit model (Naveh‐Benjamin et al, 1981), test‐anxious students often lack a repertoire of learning strategies to draw upon during exam preparation or fail to implement high‐impact practices in situations in which they would be useful. Logically, deficiencies in learning and study skills interfere with students' ability to develop an understanding of to‐be‐learned content, thereby leading to underperformance in exams (Theobald et al, 2022). Moreover, from the perspective of the emotional information processing model, students' recognition of knowledge deficits before and during evaluative events likely influences their appraisal of the learning event and subsequent affective response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evidence from Song's study suggests that there is a small but signi cant size effect of anxiety on working memory capacity. However, another crosssectional study revealed that test anxiety in medical students had no signi cant effect on exam performance (25). The complexities of this relationship necessitate additional investigation.…”
Section: Test Anxiety and Academic Achievementmentioning
confidence: 99%
“…First, retesting may represent a construct-relevant change in the underlying latent ability being measured (e.g., Roediger & Butler, 2011). Second, retesting may reduce distorting construct-irrelevant factors like motivation, test anxiety, or unfamiliarity with the test format (e.g., Freund & Holling, 2011; Matton et al, 2009; Reeve et al, 2009; though see Theobald et al, 2022). Third, retesting may allow examinees to develop better test-taking strategies that do not necessarily reflect a change in the underlying construct and may not transfer to job performance (Allalouf & Ben-Shakhar, 1998; te Nijenhuis et al, 2007).…”
Section: Diversification In the Us Armed Forcesmentioning
confidence: 99%